1994
DOI: 10.1203/00006450-199412000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor I and Insulin-like Growth Factor Binding Protein 3 as Determinants of Blood Hemoglobin Concentration in Healthy Subjects

Abstract: We studied the serum concentrations of IGF-I, IGFbinding protein 3 (IGFBP-3), and testosterone in relation to blood Hb in 60 healthy prepubertal or early pubertal boys twice, with a 9-mo interval. Serum IGF-I and testosterone levels were measured by RIA, and serum IGFBP-3 was measured by monoclonal immunofluorometric assay. Positive correlations were observed between the concentrations of blood Hb and serum IGF-I at the first examination (r = 0.36, p = 0.008) and Hb and IGFBP-3 at both examinations (r = 0 . 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 17 publications
0
28
1
2
Order By: Relevance
“…Bu dönemde demir profilaksisi önerilmek-tedir. Son olarak püberte döneminde hormonal deği-şimlere bağlı olarak kızlarda menstrüel kan kaybına bağlı demir eksikliğine eğilim erkeklerde ise yük-sek Hb değerleri görülmektedir [26,27]. Riskli gebeliklere ve doğum stresine bağlı olarak annede artan stres hormonların etkisiyle yenidoğan lökositoz ve nötrofiliye eğilimle doğar [29].…”
Section: Eri̇trosi̇tlerunclassified
“…Bu dönemde demir profilaksisi önerilmek-tedir. Son olarak püberte döneminde hormonal deği-şimlere bağlı olarak kızlarda menstrüel kan kaybına bağlı demir eksikliğine eğilim erkeklerde ise yük-sek Hb değerleri görülmektedir [26,27]. Riskli gebeliklere ve doğum stresine bağlı olarak annede artan stres hormonların etkisiyle yenidoğan lökositoz ve nötrofiliye eğilimle doğar [29].…”
Section: Eri̇trosi̇tlerunclassified
“…At this point the mean serum ferritin was 32 4 mg/kg at 24 months. The serum concentrations of IGFBP-3 (Anttila et al, 1994) and testosterone showed no correlation with serum ferritin or estimated iron stores. Nor were they associated with the preceding annual change in ferritin or iron stores.…”
Section: Resultsmentioning
confidence: 80%
“…Serum testosterone concentrations were determined by radioimmunoassay (Apter et al, 1976). In this study we also had access to the serum IGFBP-3 concentrations reported by Anttila et al (1994).…”
Section: Methodsmentioning
confidence: 99%
“…Thomsen et al (1986) found that a steep rise in haemoglobin concentration in pubescent boys took place during a short period in adolescence, soon after an increase in testosterone production. In contrast, Anttila et al (1994) in a study of younger boys, failed to find an association between serum testosterone and haemoglobin levels, but did find an association between serum IGF-1 and haemoglobin. These results imply that different systems and consequently different sets of genes may regulate red cell indices at different stages of puberty.…”
Section: Introductionmentioning
confidence: 64%
“…From childhood to adulthood, however, there is an increase in these and other indices of erythrocyte number and size. This increase is greater in males than females and is probably due to the combined action of several hormones including testosterone and insulin-like growth factor (IGF-1) that are secreted in increased amounts during adolescence (Anttila et al 1994;Thomsen et al 1986).…”
Section: Introductionmentioning
confidence: 99%